Implications of EU Accession for International Migration: An Assessment of Potential Migration Pressure - Anzelika Zaiceva (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper estimates the potential migration from eight EU accession countries as well as Bulgaria and Romania as a result of the eastern enlargement. The experience of migration from Greece, Portugal and Spain is used to estimate the parameters of a migration function, exploiting panel estimation techniques. The results from the models are then used for so-called double out of sample extrapolations - for ten countries that are not within the estimated sample and for the time period in the future. It was found that potential migration flows from central and eastern Europe will be modest. Moreover, legal introduction of free movement of workers seems not to increase migration significantly, contrary to what one might expect.
Keywords: 330; international migration; migration projections; EU enlargement; panel estimation